Letter (copy) : Goods for Spain - Tewson, Vincent
029-0086-001 HVT/FC/EK/314. Secretary's. 7th December, 1937. Mr. E. Winstanley, Export Department, Co-operative Wholesale Society Limited, 1, Balloon Street, MANCHESTER, 4. Dear Mr. Winstanley, We are desirous of sending £5,000 worth of foodstuffs to Eastern Spain. It has still to be decided as to whether the goods will be sent to Barcelona or Valencia, but probably the consignments will be divided between the two centres. I am writing to you, however, to get your views as to how the consignments could best be sent. Could you let me know whether you would recommend the definite purchase of the goods in this country to be sent by sea or whether, through your International Organisation, there is a method whereby the consignments could be purchased in this country and in France, got together in France and sent by means of a short sea passage from the South of France? We want to spend the money in the most economical way and we know that you will, from your experience, be able to help us in this matter. When I receive your reply I will again communicate with you giving further particulars of the goods required and information as to where they should be consigned. Yours sincerely, Assistant Secretary 292/946/29/86